OPTIMIZATION OF REGENERATIVE BRAKING EFFICIENCY IN ELECTRIC VEHICLES: ADVANCED CONTROL STRATEGIES AND NOVEL DYNAMIC MODELING - Mamadaliev Foziljon Abdullaevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper presents an advanced analytical study on optimizing regenerative braking efficiency in modern electric vehicles (EVs). A novel torque–based dynamic model, an adaptive energy recovery strategy, and a multi-layer control algorithm are proposed. The study incorporates new mathematical formulations, comparative tables, and conceptual system diagrams. Simulation results demonstrate that the proposed method increases overall regenerative efficiency by 18–31% under diverse road and driving conditions.